A Multifunctional Polysaccharide Utilization Gene Cluster in Colwellia echini Encodes Enzymes for the Complete Degradation of κ-Carrageenan, ι-Carrageenan, and Hybrid β/κ-Carrageenan - Line Christiansen (American Society for Microbiology, 2020)
ABSTRACT Algal cell wall polysaccharides constitute a large fraction in the biomass of marine primary producers and are thus important in nutrient transfer between trophic levels in the marine ecosystem. In order for this transfer to take place, polysaccharides must be degraded into smaller mono- and disaccharide units, which are subsequently metabolized, and key components in this degradation are bacterial enzymes. The marine bacterium Colwellia echini A3T is a potent enzyme producer since it completely hydrolyzes agar and κ-carrageenan. Here, we report that the genome of C. echini A3T harbors two large gene clusters for the degradation of carrageenan and agar, respectively. Phylogenetical and functional studies combined with transcriptomics and in silico structural modeling revealed that the carrageenolytic cluster encodes furcellaranases, a new class of glycoside hydrolase family 16 (GH16) enzymes that are key enzymes for hydrolysis of furcellaran, a hybrid carrageenan containing both β- and κ-carrageenan motifs. We show that furcellaranases degrade furcellaran into neocarratetraose-43-O-monosulfate [DA-(α1,3)-G4S-(β1,4)-DA-(α1,3)-G], and we propose a molecular model of furcellaranases and compare the active site architectures of furcellaranases, κ-carrageenases, β-agarases, and β-porphyranases. Furthermore, C. echini A3T was shown to encode κ-carrageenases, ι-carrageenases, and members of a new class of enzymes, active only on hybrid β/κ-carrageenan tetrasaccharides. On the basis of our genomic, transcriptomic, and functional analyses of the carrageenolytic enzyme repertoire, we propose a new model for how C. echini A3T degrades complex sulfated marine polysaccharides such as furcellaran, κ-carrageenan, and ι-carrageenan. IMPORTANCE Here, we report that a recently described bacterium, Colwellia echini, harbors a large number of enzymes enabling the bacterium to grow on κ-carrageenan and agar. The genes are organized in two clusters that encode enzymes for the total degradation of κ-carrageenan and agar, respectively. As the first, we report on the structure/function relationship of a new class of enzymes that hydrolyze furcellaran, a partially sulfated β/κ-carrageenan. Using an in silico model, we hypothesize a molecular structure of furcellaranases and compare structural features and active site architectures of furcellaranases with those of other GH16 polysaccharide hydrolases, such as κ-carrageenases, β-agarases, and β-porphyranases. Furthermore, we describe a new class of enzymes distantly related to GH42 and GH160 β-galactosidases and show that this new class of enzymes is active only on hybrid β/κ-carrageenan oligosaccharides. Finally, we propose a new model for how the carrageenolytic enzyme repertoire enables C. echini to metabolize β/κ-, κ-, and ι-carrageenan.